Prevalência e correlatos clínicos e funcionais parkinsonismo em amostra populacional de idosos muito idosos (> 75 ANOS): estudo Pietá - Thiago Cardoso Vale (2019)
INTRODUCTION: Brazil is considered one of the developing countries with the highest rates of population aging and the growth of the population aged 75+ years, known as the oldest-old individuals, deserves special mention. One of the consequences of this process of demographic transition is the high prevalence of neurodegenerative and psychiatric chronic diseases, including dementia, parkinsonism and depression. There are only a few epidemiological studies involving the oldest-old population in Latin America, especially in Brazil. OBJECTIVES: To estimate the prevalence and to define etiologies of parkinsonian syndrome in a population-based sample of community-dwelling oldest-old individuals. To compare the clinical, psychiatric, cognitive comorbidities and the functional status of individuals with parkinsonism vs. individuals without parkinsonism from the same population. METHODS: The Pietà study is a population-based investigation on brain aging in an oldest-old sample. It was conducted in Caeté (MG), in the Southeast of Brazil, during the period of January to April 2008, and involved 639 individuals aged 75+ years. The first two phases of the study involved the collection of sociodemographic and clinical data through a structured clinical interview aided by the application of questionnaires. The third phase comprised physical and neurological examination with application of validated scales for motor, cognitive, psychiatric and functional evaluations. Univariate and multivariate comparative analysis between parkinsonian and non-parkinsonian groups and with outcomes of functional loss were carried out. RESULTS: Sixty-five individuals with parkinsonism were identified (women [61.5%], with median age and schooling of, respectively, 82.0 years and 2.0 years) and then compared to 542 individuals without parkinsonism (women [64.8%] with median age and schooling of, respectively, 80.0 years 3.0 years). Prevalence of parkinsonism was 10,656 per 100,000 individuals (95% CI: 8,321-13,380). Parkinsons disease, parkinsonian-dementia syndrome, drug-induced parkinsonism, vascular parkinsonism and dementia with Lewy-bodies were identified in, respectively, 19 (29.2%), 19 (29.2%), 8 (12.3%), 4 (6.1%) and 1 (1.5%) individuals from the sample. Fourteen individuals (21.5%) could not have their parkinsonian etiology identified. The parkinsonian sample had more functional impairment (Pfeffers score of 7.0 points versus 1.0 point and FAST staging of 4.0 points versus 0.0 points; p< 0.001), more clinical comorbidities (including the number of falls, abnormal sphincter control and dysphagia) and depression (21 [32.3%] versus 113 [21.0%]; p=0.038). The parkinsonian sample had a significantly worse cognitive performance in the Mini- Mental State Examination, category fluency test, clock-drawing and delayed recall in a memory test, with median (interquartile range) of, respectively, 18 (13-21) points, 7 (5-10) points, 1 (1-4) point and 4 (2-7) points. Dementia was significantly more frequent in the parkinsonian sample, being diagnosed in 37 (56.9%) individuals. Vascular risk factors, including hypertension, diabetes and dyslipidemia, had similar distribution among both groups. Multivariate analysis revealed that age, higher scores on the motor section of the UPDRS scale and lower scores on the verbal fluency and delayed recall in a memory test were independently associated with the outcome of being in the parkinsonian group. CONCLUSION: This community-based sample of oldest-old presented a high estimated prevalence of parkinsonism, being Parkinsons disease followed by a parkinsonian-dementia syndrome the most frequent causes. Etiologic classification of parkinsonism was challenged by many factors, such as the lack of clinical data, chronology of symptoms, longitudinal evaluation, neuroimaging data and the concomitance of drugs with potential to cause parkinsonism. The parkinsonian sample had significantly more clinical, cognitive and psychiatric comorbidities with functional impairment when compared to individuals without parkinsonism. Age and reduced motor and cognitive performance were independently associated with parkinsonism